rút gọn (x-10)^2 -x.(x+80)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)(x-10)2-x(x+80)
(x2-2x10+100)-x2-80x
=x2-20x+100-x2-80x=-100x+100
khi x = 0.98
ta có
(-100*0.98)+100=-98+100=2
b)x3-9x+27x-27
hình như là -27x :))
![](https://rs.olm.vn/images/avt/0.png?1311)
a, (x-10)^2-x(x+80)
=x2-20x+100-x2-80x
=-100x+100
Thay x=0,98
=-100.0,98+100
=2
b, (2x+9)^2-x(4x+31)
=4x2+36x+81-4x2-31x
=5x+81
Thay x=16,2
=5.16,2+81
=162
c, 4x^2-28x +49
=(2x)2-2.2x7+72
=(2x-7)2
Thay x=4
=(2.4-7)2
=12
=1
đ, x^2-9x^2+27x-27
=k bt lm
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x-10\right)^2-2\left(x-10\right)\left(5x-3\right)+\left(5x-3\right)^2\)
\(=\left(x-10-5x+3\right)^2=\left(-4x-7\right)^2=\left(4x+7\right)^2\)
\(=16x^2+56x+49\)
Ta có: \(\left(x-10\right)^2-2\left(x-10\right)\left(5x-3\right)+\left(5x-3\right)^2\)
\(=\left(x-10-5x+3\right)^2\)
\(=\left(-4x+6\right)^2\)
\(=16x^2-48x+36\)
\(x^2-20x+100-x^2-80x\)
\(100-100x\)
\(100\left(1-x\right)\)